Particleboard Made From Modified Crosslinked Carboxymethyl Starch From Oil Palm Trunk As Bio-Adhesives - Selamat, Mohd Ezwan (2014)
The compatibility of modified crosslinked carboxymethyl oil palm trunk starch as the new natural based adhesive for wood-based composite was studied through a numbers tests such as proximate analysis, physical and mechanical test. The starch was extracted from oil palm trunks which are more than 25 years old oil palm trees due to the decreased fruits yield and the difficulty for harvesting process Kesesuaian kanji batang kelapa sawit modifikasi silang paut karboksimetil sebagai perekat baru berasaskan sumber semulajadi untuk komposit berasaskan kayu dilakukan melalui beberapa ujian seperti analisis proksimat, sifat fizikal dan mekanikal. Kanji diekstrak daripada batang kelapa sawit yang berusia melebihi 25 tahun yang mana buahnya telah berkurangan dan proses penuaian yang sukar.